(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Today’s professional women seek to reconcile the different environments and spaces in their lives and to achieve this, they need to set priorities, which implies choosing and giving up certain things according to their primary reason of existence. The purpose of this study is to identify the losses that professional women have had throughout their lives and the way they cope with them. The study was developed through an interpretative paradigm with a qualitative approach; the method used was the phenomenological narrative. Eleven women were interviewed in depth, where the main findings were the difference between losses and renunciations, among them: separations, self-forgetfulness, work, and deaths. The ways of coping with that are: spirituality, pain management, emotional intelligence. The meaning of life, resilience and support networks stand out in the women’s discourse.